Magnetically actuated sonodynamic nanorobot collectives for potentiated ovarian cancer therapy - Zhou, Yixuan; Cao, Ziqi; Jiang, Lixian; Chen, Ying; Cui, Xiaoyu; Wu, Jianrong; Xie, Xue; Wang, Longchen; Ying, Tao (Frontiers in Bioengineering and Biotechnology, 2024)
Ovarian cancer presents a substantial challenge due to its high mortality and recurrence rates among gynecological tumors. Existing clinical chemotherapy treatments are notably limited by drug resistance and systemic toxic side effects caused by off target drugs.Sonodynamic therapy (SDT) has emerged as a promising approach in cancer treatment, motivating researchers to explore synergistic combinations with other therapies for enhanced efficacy. In this study, we developed magnetic sonodynamic nanorobot (Fe3O4@SiO2-Ce6, FSC) by applying a SiO2 coating onto Fe3O4 nanoparticle, followed by coupling with the sonosensitizer Ce6. The magnetic FSC nanorobot collectives could gather at fixed point and actively move to target site regulated by magnetic field. In vitro experiments revealed that the magnetic FSC nanorobot collectives enabled directional navigation to the tumor cell area under guidance. Furthermore, under low-intensity ultrasonic stimulation, FSC nanorobot collectives mediated sonodynamic therapy exhibited remarkable anti-tumor performance. These findings suggest that magnetically actuated sonodynamic nanorobot collectives hold promising potential for application in target cancer therapy.